Complexes of peracetylated cyclodextrin in a non-aqueous aprotic medium: the role of residual water1. Issue 26 (14th July 2015) - Jicsinszky, Laszlo; Martina, Katia; Caporaso, Marina; Cintas, Pedro; Zanichelli, Andrea; Cravotto, Giancarlo
<x xml:space="preserve">Abstract</x> Not all peracetylated cyclodextrins can be completely dried and water protons can be invisible due to the overlapping signals of the acetyl groups. Apparent stability constants of complexes were also calculated.